LITERATURE REVIEW: EFEKTIVITAS SHOLAT TAHAJJUD DALAM MENINGKATKAN PRESTASI AKADEMIK - Mohammad Ali Wafa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education is a path to acquiring better knowledge, attitudes, and behaviors for a better life and future. Every student hopes to achieve good academic performance. Good performance is influenced by balanced multiple intelligences. Spiritual quotient (SQ) is an intelligence that encompasses other multiple quotients. One of the activities related to SQ is performing the Tahajjud prayer, which is expected to improve students’ academic performance.The purpose of this study is to determine the effectiveness of the Tahajjud prayer in improving academic performance. The research method used is qualitative with a literature review approach. The results of this study indicate that the Tahajjud prayer is linked to improving academic performance from various perspectives. The Tahajjud prayer is able to provide peace of mind, reduce stress, and enhance affective, cognitive, and psychomotor intelligences, ultimately leading to better academic performance.